IMPLEMENTASI KARTU MEMBER PADA APLIKASI POINT OF SALES BERBASIS WEB DALAM MENDUKUNG PROGRAM PKH (STUDI KASUS : TOKO MENIKWATI) - Dikky Wahyudi; Suprihadi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Store is a place where buying and selling transactions between sellers and buyers. However not everyone can buy the things needed to fulfil of their daily needs, especially for families bear status of poor families. This raises various problems even do criminal acts in order to fulfil their needed. On the other hand one of the government’s goals is reduce the poverty rate. Based on the core of problem, this research focuses on implementing member cards on web-based point of sales applications to support of the PKH program (Case Study : Menikwati Store). It is hoped this application can help prosper the economoy for families with poor family status, overcome poverty, and support the PKH program to successfully. The development of this point of sales application use waterfall method, with the programming language used is PHP, JavaScript, Ajax and Laravel Framework. For application testing using User Acceptance Test (UAT) with the black box testing.